Case report of a rare case of meibomian gland carcinoma of the lower eyelid - Devi, Bhanu; Das, Rajiv Kumar; Medhi, Santana (International Journal of Research in Medical Sciences, 2017)
The sebaceous gland carcinoma is a very rare, highly malignant tumour of the eyelid arising from sebaceous glands of the eyelid such as meibomian glands, glands of Zeis, and caruncle. The tumour is more commonly seen in elderly females and more commonly involve the upper eyelid. We present a rare case of meibomian gland carcinoma of the left lower eyelid in a 59-year-old female who came with a history of a slow growing painless swelling of the lower eyelid. Histopathological examination confirmed poorly differentiated meibomian gland carcinoma.